2012
DOI: 10.1177/0011392112459744
|View full text |Cite
|
Sign up to set email alerts
|

Gender representation in school textbooks in Iran: The place of languages

Abstract: This article focuses on the association between language and gender from a sociological perspective. The article provides research-based evidence to analyse whether and to what extent gender characteristics represented through the educational system are associated with the languages used in the educational resources. The analysis uses socialization theory which recognizes the educational system, particularly the school and its educational materials, as the first official agent and the most powerful engine of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 37 publications
6
42
0
5
Order By: Relevance
“…Therefore, it is acknowledged that a wide range of factors contributed to the women's birth fall in Iran during the recent years 6 . However, the results of this study, in accordance with prior studies (Abbasi-Shavazi, 2009;Foroutan, 2012, Foroutan, 2014Hosseini-Chavoshi et al, 2016;Ladier-Fouladi, 1997;McDonald et al, 2015), emphasize that the spectacular fertility transition in Iran mainly lies in different socio-cultural views and values contributed by the old and new generations.…”
Section: Generational Gap In Fertility Patternsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, it is acknowledged that a wide range of factors contributed to the women's birth fall in Iran during the recent years 6 . However, the results of this study, in accordance with prior studies (Abbasi-Shavazi, 2009;Foroutan, 2012, Foroutan, 2014Hosseini-Chavoshi et al, 2016;Ladier-Fouladi, 1997;McDonald et al, 2015), emphasize that the spectacular fertility transition in Iran mainly lies in different socio-cultural views and values contributed by the old and new generations.…”
Section: Generational Gap In Fertility Patternsupporting
confidence: 90%
“…Generally speaking, the traditional beliefs predominant amongst the old generation in Iran could be identified by a wide range of gender preference at which male gender is often prioritized to female gender (Foroutan, 2012;Foroutan, 2019). Such cultural beliefs have been demonstrated in different ways, which are classified in three main groups in this study.…”
Section: Generational Change In Gender (Sex) Preferencementioning
confidence: 93%
“…Before the 1979 Revolution, the educational system was secular. However, after the revolution, the educational system as well as schools, were changed fundamentally and are currently based on Islamic values (Foroutan, 2012). This change came to force in the 1987 Education Law, which ‘gives priority to ethical and religious development in educational and school activities' (Paivandi, 2008: 9) and it is considered to be part of the process of Islamisation of schools (Foroutan, 2012).…”
Section: Elt In the Islamic Republic Of Iranmentioning
confidence: 99%
“…Chen and Rao (2011) suggested that teachers' contributions on gender socialization in Chinese Kindergartens directly impacts children through picture book representations delivered by educators. In fact, it is necessary to investigate gender representation in other reading materials, such as textbooks (Foroutan 2012) and picture books, which convey gender messages to young children (Nair and Rosli 2013). Liang, O'Halloran, and Tan (2016) explored the metaphors used for sex education in picture books from China.…”
Section: (B) Geographic Distributionmentioning
confidence: 99%